Contribution and limits of clinical specimens for the screening of intestinal multi-drug-resistant bacteria in view of laboratory automation. Issue 1 (September 2017) - Geraud de Galassus, A.; Cizeau, F.; Agathine, A.; Domrane, C.; Ducellier, D.; Fihman, V.; Decousser, J-W.
Summary: The detection of multi-drug-resistant bacteria carriers constitutes a race against time for infection preventionists. Alongside standard analysis for diagnostic purposes and a rectal screening strategy, the authors tested a heavy-loaded selective method against 562 clinical specimens from 439 patients to detect extended-spectrum beta-lactamase-producing (ESBL) or carbapenemase-producing Enterobacteriaceae (CPE) and vancomycin-resistant enterococci (VRE). The approach identified five more specimens positive for ESBL-producing Enterobacteriaceae than standard analysis, and six out of nine known VRE/CPE carriers (three new CPE/VRE strains were also identified in this cohort). In view of the ongoing automation of laboratories, this approach focusing on urine and stool specimens may be an alternative or complementary approach to dedicated rectal screening.